Pneumatic fertilizer distribution an exploratory study - Zubia, Omar F. (Philippine agricultural mechanization journal)
Fertilizer distribution is still done manually in rice farming. Broadcasting with a machine is more accurate and rapid than when done by hand. A research was conducted to explore the use of pneumatic system in fertilizer distribution. Test results showed that granular fertilizer can be successfully quantified by the designed metering mechanism. Providing a good control tot he discharge lever can produce a relatively good degree of discharge rate variation, as reflected by 3.55 percent to 9.30 percent CV. The results are within limit of the design parameter set at 10 percent. There was a high degree of variability of distribution, averaging between 37.1 percent and 52 percent for different opening setting. A distribution characteristic has been laid out and the concentration of fertilizer over an area is already been identified. It is recommended to further study the concept to improve the system.